2019
DOI: 10.1016/j.stemcr.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific iPSC Model of a Genetic Vascular Dementia Syndrome Reveals Failure of Mural Cells to Stabilize Capillary Structures

Abstract: CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is the most common form of genetic stroke and vascular dementia syndrome resulting from mutations in NOTCH3. To elucidate molecular mechanisms of the condition and identify drug targets, we established a patient-specific induced pluripotent stem cell (iPSC) model and demonstrated for the first time a failure of the patient iPSC-derived vascular mural cells (iPSC-MCs) in engaging and stabilizing endothelial capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 44 publications
(60 reference statements)
1
54
0
Order By: Relevance
“…The current study showed that increased PDGFRβ in CADASIL MCs resulted in cellular proliferation at significantly lower PDGF-BB concentration. However, a recent study by Kelleher et al [37] reported decreased PDGFRβ in CADASIL iPSC (p.Arg153Cys and p.Cys224Tyr)-derived MCs. Although our study used CADASIL iPSCs with different NOTCH3 mutations from theirs, they are all located in exon3/4.…”
Section: Discussionmentioning
confidence: 92%
“…The current study showed that increased PDGFRβ in CADASIL MCs resulted in cellular proliferation at significantly lower PDGF-BB concentration. However, a recent study by Kelleher et al [37] reported decreased PDGFRβ in CADASIL iPSC (p.Arg153Cys and p.Cys224Tyr)-derived MCs. Although our study used CADASIL iPSCs with different NOTCH3 mutations from theirs, they are all located in exon3/4.…”
Section: Discussionmentioning
confidence: 92%
“…The upregulated expression of genes linked to the NF-kB pathway was identified, indicating that an inflammatory response may be involved. Another recent study using patient-derived iPSCs showed that CADASIL mutant Notch3 mural cells failed to stabilise endothelial networks (also iPSC-derived) in a co-culture model, unlike wild-type VSMCs [107]. The CADASIL VSMCs were also more prone to apoptosis.…”
Section: Notch3 and Cerebral Autosomal Dominant Arteriopathy With Submentioning
confidence: 98%
“…Clear phenotypes are restricted to the brain, but several studies suggested cardiovascular (van den Boom et al, 2003;Rufa et al, 2007) and renal (Kusaba et al, 2007;Guerrot et al, 2008;Ragno et al, 2012) involvement, though their causal relationship is still unclear. A recent article by Kelleher et al (2019) showed that CADASIL iPSC-derived mural cells, including VSMCs and pericytes were susceptible to apoptotic stress. This may explain why major symptoms are restricted to the brain, because the blood-brain barrier, the crucial structure to maintain brain homeostasis, consists of astrocytes and pericytes (Ihara and Yamamoto, 2016).…”
Section: Why Clinical Symptoms Occur Only In the Brainmentioning
confidence: 99%